Lazarus without limits scripture, tradition and the cultural life of a text - Loades, Ann 1938-2022 (2018)
The "raising of Lazarus" is integrally connected with "the harrowing of hell" in those liturgical traditions which rightly value the linkage between the two for reflection on the scope and meaning of Christ's saving work. To neglect one or the other turns "Holy Saturday" into a liturgical and spiritual "blank" instead of a time of appropriate ways of reflection in respect of the horrors and griefs of our times and what may lie beyond them. Extraordinarily, however, those whose engagement with the realities around them is via the 'arts', continue to focus on either or both of Lazarus and the "harrowing of hell" and become the "theologians" for our times.
Keywords: Cana and Bethany; Eastern and Western traditions; Lazarus; biblical text to liturgy; Death; from Yeats to Bowie; poets and theologians (twenty - twenty-first centuries); Resurrection; the harrowing of hell